واقع تعليمية اللغة العربية حاسوبيا في ظل جائحة كورونا المرحلة الجامعية أنموذجا دراسة تطبيقية في جامعة الوادي - نوري، ياسين, طلحة، مسعودة (University of El-oued, 2022)
مما سبق وبعد البحث والاطلاع استنتجنا أن اللسانيات الحاسوبية علم بيني يتكون من اللسانيات والحاسوب. وهي الاستعمال الدقيق للحاسب الآلي لإجراء بعض العمليات الرياضية فيه، والتي تشبه العمليات المنطقية الرياضية التي يقوم بها الذهن الإنساني بهدف أن يهيئ للحاسوب كفاية لغوية مثل الإنسان، حيث يستقبل اللغة ويفهمها ثم يعيد إنتاجها. وتعد دراسة اللغة العربية باستخدام اللسانيات الحاسوبية من أحدث الاتجاهات اللغوية في اللسانيات المعاصرة، فقد عالجت العربية آليا في شتى المجالات وهذا ما جعلها ترقى وتواكب العصرنة شأنها شأن الانجليزية وغيرها من اللغات. كما يعد الحاسوب من الوسائل التعليمية المهمة والمستخدمة في تدريس مختلف مهارات اللغة العربية، وقد دخل مجالات التعليم والتعلم من أبوابه الواسعة باعتباره وسيلة من الوسائل المعينة، وطريقة متطورة لإيصال المعلومات والمعارف، وهذا يشجع الباحث على الاستعانة به في ميدان تعلم اللغة وتعليمها ن وتحديث طرائق تدريسها. أيضا نجد أن اللسانيات الحاسوبية فتحت آفاقا جديدة في مجال التعليم وطورت العملية التعليمية، وساعدت على توفير بيئة تعليمية مناسبة تتيح للمتعلم الاستفادة من أنواع متعددة ومختلفة من مصادر التعلم، كما خلقت أنماطا جد متطورة للتعليم "كالتعليم الالكتروني" الذي أحدث غزو عالمي، وكان حلا بديلا للأنماط التقليدية المعتمدة في التدريس، وكذا كان الحل الأمثل لمواصلة الدراسة في ظل جائحة كورونا في العديد من الدول. وبالرغم من نجاح هذه التجربة أثناء تطبيقها إلا أن الجزائر لم تحقق النجاح نتيجة عدة عوامل منها: • قلة تدفق الإنترنت في بعض أنحاء الوطن. • ندرة توفر البرامج التعليمية باللغة العربية حيث يشكل هذا الأمر عقبة في توسع استخدام الحاسوب في التعليم. • قلة البرامج الحاسوبية الملائمة ذات المستوى الرفيع بسبب الجهد الكبير المطلوب لتصميم البرامج وكتابتها. ومن المعيقات أيضا مشكلات تتعلق باختيار استراتيجيات التدريس المناسبة للتعامل مع الحاسوب كمادة تعليمية وكوسيلة تعليمية أيضا. لهذا وجب على الدولة الجزائرية الاهتمام أكثر بهذا المجال وإجراء دراسات حول الموضوع من أجل إصلاح المنظومة التربوية، وتطوير مجال التعليم من الطور الابتدائي إلى التعليم الجامعي، وبالتالي الرقي بمستوى التعليم في الجزائر. From the above and after research and reading, We concluded that computer linguistics is a Bene science consisting of linguistics and computer. It is the precise use of a computer to perform some mathematical operations in it, which are similar to the mathematical logical operations carried out by the human mind in order to prepare the computer linguistic adequacy like a human, where it receives and understands the language and then reproduces it. The study of the Arabic language using computer linguistics is one of the latest linguistic trends in contemporary linguistics, it has treated Arabic automatically in various fields and this has made it rise and keep pace with the modernization like English and other languages. The computer is also one of the important teaching methods used in teaching various Arabic language skills, and has entered the fields of teaching and learning from its wide doors as a means of particular means, and a sophisticated way to communicate information and knowledge, and this encourages the researcher to use it in the field of language learning and teaching and updating methods of teaching. We also find that computer linguistics has opened new horizons in the field of education and developed the educational process, and helped to provide an appropriate learning environment that allows the learner to benefit from multiple and different types of learning resources, and created very advanced patterns of education "e-learning", which has caused a global invasion, and was an alternative solution to the traditional patterns adopted in teaching, as well as the best solution to continue studying in light of the corona pandemic in many countries. Despite the success of this experiment during its implementation, Algeria has not achieved success due to several factors, including: * Lack of internet access in some parts of the country. * The scarcity of educational programs in Arabic, as this is an obstacle to the expansion of computer use in education. * Lack of appropriate high-level software due to the considerable effort required to design and write software. Problems with the selection of appropriate teaching strategies for dealing with computers as a teaching material as well as a teaching medium are also a constraint. Therefore, the Algerian state should pay more attention to this area and conduct studies on the subject in order to reform the educational system, develop the field of education from primary to university education, and thus improve the level of education in Algeria.